2023
DOI: 10.1128/mbio.00078-23
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variant Pathogenesis Following Primary Infection and Reinfection in Syrian Hamsters

Abstract: With the continued circulation and emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants, understanding differences in the effects between the initial infection and a subsequent reinfection on disease pathogenesis is critical and highly relevant. This study characterizes Syrian hamsters as an animal model to study reinfection with SARS-CoV-2. Previous infection reduced the disease severity of reinfection with different SARS-CoV-2 variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The body weight measurement at different time points showed a body weight loss of up to 5% in both sexes of the animals up to 4 dpi followed by a gain in body weight. Previous studies have shown that the SARS-CoV-2 infection in hamsters is associated with clinical manifestations such as reduced body weight up to 7 dpi followed by recovery [19,26,27]. Further, it has been observed that the change in body weight in hamsters is associated with virus inoculum dose rather than the age of the animal [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The body weight measurement at different time points showed a body weight loss of up to 5% in both sexes of the animals up to 4 dpi followed by a gain in body weight. Previous studies have shown that the SARS-CoV-2 infection in hamsters is associated with clinical manifestations such as reduced body weight up to 7 dpi followed by recovery [19,26,27]. Further, it has been observed that the change in body weight in hamsters is associated with virus inoculum dose rather than the age of the animal [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The Syrian golden hamster has become the preclinical animal model of choice to assess vaccine effectiveness against SARS-CoV-2 variants, as well as the likelihood of reinfections ( 16 , 21 28 ). Such information is critical for rational decisions around vaccine strain updates or other public health responses to the continuing emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al saw BA.1 reinfections of hamsters infected 50 d earlier with first-wave virus but puzzlingly also recorded reinfection with homologous virus at that time interval ( 26 ). Similarly, Plunkard et al readily reinfected hamsters with BA.1 following first infections with a variety of different variants of concern ( 28 ). However they did not record virology outputs in their study but used weight loss as an indicator of infection making comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For hamster infection, SARS-CoV-2 in 100 μL DMEM was intranasally inoculated to hamsters (50 μL per nare). Reported viral inoculation doses ranged from 1 × 10 2 to 1 × 10 7 TCID 50 /mL (38,69,(83)(84)(85)(86) in the literature for different study purposes. However, an ideal dose should mimic the uniform infection in human olfactory epithelium, as displayed in patients with COVID (Figure 5 and 6, by Khan, et al) (5).…”
Section: Methodsmentioning
confidence: 99%